(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article deals with the the semantic characteristics of the Belarusian and German somatic phraseological units representing emotions. The phraseological activity of somatic lexemes is revealed, phraseological units with high-frequency somatic components are analyzed. The type of interlingual phraseological equivalence is determined. Full equivalents are identified, characterized by the same semantics, component composition, and similar structure; partial equivalents having the same meaning, similar or different structure and different component composition; non-equivalent phraseological units, characterized by the absence of direct analogs in the language of comparison. The general and specific in the meaning and functioning of stable units of two languages are determined. As the examples show, somatic phraseologies in both Belarusian and German represent mostly negative emotions, such as fear, shame, sadness, anger, envy, despair. Positive emotions are transmitted much less often. This reflects the similarity of the Belarusian and German language picture of the world. National distinctiveness is manifested in the absence of exact equivalents, which is explained by both linguistic and extralinguistic factors. It is noted that the phraseologisms of the two languages have a high interlingual equivalence. This is due to the fact that these components are part of the common and ancient vocabulary of each language, equally understood in the culture of these countries and have a high phrase-forming activity. These factors increase the degree of interlingual equivalence. Thus, a comparative analysis of phraseological units allowed us to elucidate some universal and specific features of stable units of two languages. The actual material will be useful in compiling a translation dictionary of somatic phraseology, in teaching special courses on translation practice.